Impaired motility in Barrett's esophagus: A study using high‐resolution manometry with physiologic challenge. Issue 8 (15th March 2018) - Sanagapalli, S.; Emmanuel, A.; Leong, R.; Kerr, S.; Lovat, L.; Haidry, R.; Banks, M.; Graham, D.; Raeburn, A.; Zarate‐Lopez, N.; Sweis, R.
Abstract: Background: Esophageal dysmotility may predispose to Barrett's esophagus (BE). We hypothesized that high‐resolution manometry (HRM) performed with additional physiologic challenge would better delineate dysmotility in BE. Methods: Included patients had typical reflux symptoms and underwent endoscopy, HRM with single water swallows and adjunctive testing with solids and rapid drink challenge (RDC) before ambulatory pH‐impedance monitoring. BE and endoscopy‐negative reflux disease (ENRD) subjects were compared against functional heartburn patient‐controls (FHC). Primary outcome was incidence of HRM contractile abnormalities with standard and adjunctive swallows. Secondary outcomes included clearance measures and symptom association on pH‐impedance. Key Results: Seventy‐eight patients (BE 25, ENRD 27, FHC 26) were included. Water swallow contractility was reduced in both BE (median DCI 87 mm Hg/cm/s) and ENRD (442 mm Hg/cm/s) compared to FHC (602 mm Hg/cm/s; P  < .001 and .04, respectively). With the challenge of solid swallows and RDC, these parameters improved in ENRD (solids = 1732 mm Hg/cm/s), becoming similar to FHC (1242 mm Hg/cm/s; P  = .93), whereas abnormalities persisted in BE (818 mm Hg/cm/s; P  < .01 c.f. FHC). In BE and ENRD, reflux events (67 vs 57 events/24 hour) and symptom frequency were similar; yet symptom correlation was significantly better in ENRD compared to BE, which was comparable to FHC (symptom index 30% vs 4% vs 0%, respectively). Furthermore, bolus clearance and exposure times were more pronounced in BE ( P  < .01). Conclusions & Inferences: Reduced contractile effectiveness persisted in BE with the more representative esophageal challenge of swallowing solids and free drinking; while in ENRD and FHC peristalsis usually improved, demonstrating peristaltic reserve. Furthermore, symptom association and refluxate clearance were reduced in BE. These factors may underlie BE pathogenesis. Abstract : Esophageal dysmotility is implicated in the pathogenesis of Barrett's esophagus, but has not been studied following solids and rapid drink challenge, which more accurately replicate normal swallowing behavior. With standard HRM using 5mL water swallows, esophageal body contractility was similarly poor in both Barrett's and endoscopy‐negative reflux disease. When challenged with solids and the rapid drink challenge however, contractility normalized in endoscopy‐negative reflux patients; whereas in Barrett's esophagus it remained just as impaired.